TiB2 / Al-Cu alloy, preparation method thereof and application of TiB2 / Al-Cu alloy in additive manufacturing
TiB2/Al-Cu alloy is prepared by magnetic field vibration assisted mechanical stirring, and trace alloying elements are added during the smelting process, which solves the defects and problems of Al-Cu alloy in the casting process and improves laser absorption and mechanical properties , suitable for additive manufacturing complex components.
Patent Information
- Application Number
- CN202411491939.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-24
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-10-24
AI Technical Summary
Al-Cu alloys are prone to defects such as looseness, thermal cracking and oxidative inclusions during casting, and their laser absorption is low, making it difficult to carry out efficient laser additive manufacturing.
TiB2/Al-Cu alloy is prepared by in-situ self-generating method with magnetic field vibration assisted mechanical stirring, which promotes the uniform dispersion of micro-nano TiB2 particles, and adds trace alloying elements such as Mn, Zr/Y during the smelting process to refine them. Die grains and improve mechanical properties.
It effectively improves the laser absorption rate of alloys in the additive manufacturing process, improves mechanical properties and corrosion resistance, reduces structural defects, and is suitable for forming complex components with additive manufacturing.
Smart Images

Figure CN119410977A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of additive manufacturing materials, and in particular to a TiB2 / Al-Cu alloy, a preparation method thereof, and additive manufacturing applications. Background Art
[0002] Al-Cu alloy has the characteristics of low density, high specific strength and specific stiffness, good plasticity, excellent thermal conductivity, and corrosion resistance. It has become the preferred material for achieving lightweight structures of high-end key equipment and has broad application prospects in the fields of aerospace and ship equipment. However, due to the wide solidification temperature range, Al-Cu alloy has poor casting performance, especially a large tendency to thermal cracking, shrinkage and shrinkage cavity, and the components are highly sensitive to wall thickness. Defects such as looseness, thermal cracking and oxidation inclusions are easily generated during the casting process. The low laser absorption rate also makes it difficult to perform laser additive manufacturing (also known as 3D printing).
[0003] At present, the methods used to improve the forming quality and mechanical properties of 3D printed Al-Cu alloys mainly include: 1. The method of introducing heterogeneous particles into aluminum alloy powder through electrostatic self-assembly, high-energy ball milling, aerosol delivery adhesive and ultrasonic vibration dispersion technology, such as nano ZrH, TiC, TiB2, TiN and SiC particles, etc. These heterogeneous particles can effectively improve the laser absorption rate of aluminum powder, change the evolution process of molten pool solidification structure, play a role in dispersion strengthening, and significantly improve the mechanical properties of 3D printed aluminum alloys. However, these preparation methods are generally complex, and heterogeneous particles are difficult to disperse uniformly in the form of nanoparticles, which are easy to introduce other impurities that are difficult to remove, or destroy the sphericity of aluminum powder and reduce powder fluidity. This method can achieve good results in the experimental stage, but it is difficult to achieve mass production, which limits its industrial application. 2. Regulate the chemical composition of aluminum powder during the aerosol preparation process, and change the physical properties of aluminum alloys through microalloying design to adapt them to the extremely non-equilibrium metallurgical process of 3D printing. Summary of the invention
[0004] Due to the above-mentioned defects in the prior art, the present invention provides a TiB2 / Al-Cu alloy, a preparation method and an additive manufacturing use thereof. The TiB2 / Al-Cu alloy is prepared by an in-situ autogenous method of a mixed salt with magnetic field vibration assisted mechanical stirring, which is beneficial to promoting the uniform dispersion of micro-nano TiB2 particles formed in the material, exerting the heterogeneous nucleation and reinforcement effects of the particles, and can effectively improve the laser absorption rate of the alloy in the additive manufacturing process; trace alloying elements such as Mn, Zr / Y are added during the smelting process, which can refine the grains during the alloying process and improve the mechanical properties and corrosion resistance of the material.
[0005] To achieve the above object, in a first aspect, the present invention provides a method for preparing a TiB2 / Al-Cu alloy and a TiB2 / Al-Cu alloy prepared therefrom, characterized in that, in terms of mass fraction, the TiB2 / Al-Cu alloy components include Cu: 1-5%; Mn: 0.1-0.3%; TiB2: 1-8%, and the balance is Al; and the preparation process comprises the following steps:
[0006] Step S1, according to the composition ratio of the TiB2 / Al-Cu alloy, high-purity Al, Al-Cu master alloy and Al-Mn master alloy are placed in a melting crucible and melted into a melt;
[0007] Step S2, heating the melt to 760-850°C, adding KBF4 and K2TiF6 mixed salt according to the composition ratio of the TiB2 / Al-Cu alloy, applying a transverse eddy current magnetic field with a current intensity not exceeding 20A, and performing mechanical stirring; then casting the melt at 720-740°C to obtain a TiB2 / Al-Cu alloy ingot.
[0008] In a second aspect, the present invention provides a method for preparing a TiB2 / Al-Cu alloy and a TiB2 / Al-Cu alloy prepared therefrom, characterized in that, in terms of mass fraction, the TiB2 / Al-Cu alloy components include Cu: 1-5%; Mn: 0.1-0.3%; Zr: 0.1-0.3%; TiB2: 1-8%, and the balance is Al; the preparation process comprises the following steps:
[0009] Step S1, according to the composition ratio of the TiB2 / Al-Cu alloy, high-purity Al, Al-Cu master alloy, Al-Mn master alloy, and Al-Zr master alloy are placed in a melting crucible and melted into a melt;
[0010] Step S2, heating the melt to 760-850°C, adding KBF4 and K2TiF6 mixed salt according to the composition ratio of the TiB2 / Al-Cu alloy, applying a transverse eddy current magnetic field with a current intensity not exceeding 20A, and performing mechanical stirring; then casting the melt at 720-740°C to obtain a TiB2 / Al-Cu alloy ingot.
[0011] In a third aspect, the present invention provides a method for preparing a TiB2 / Al-Cu alloy and a TiB2 / Al-Cu alloy prepared therefrom, characterized in that, in terms of mass fraction, the TiB2 / Al-Cu alloy components include Cu: 1-5%; Mn: 0.1-0.3%; Y: 0.1-0.3%; TiB2: 1-8%, and the balance is Al; and the preparation process comprises the following steps:
[0012] Step S1, according to the composition ratio of the TiB2 / Al-Cu alloy, high-purity Al, Al-Cu master alloy and Al-Mn master alloy are placed in a melting crucible and melted into a melt;
[0013] Step S2, heating the melt to 760-850° C., adding KBF4 and K2TiF6 mixed salt according to the composition ratio of the TiB2 / Al-Cu alloy, applying a transverse eddy current magnetic field with a current intensity of no more than 20A, and performing mechanical stirring;
[0014] Step S3, cooling the melt to 700-710°C, adding Al-Y master alloy according to the composition ratio of the TiB2 / Al-Cu alloy, continuously applying a transverse eddy current magnetic field and mechanical stirring, and adding an amount of Al-Y master alloy to increase the burnout amount on the basis of the rated addition amount; then casting the melt at 720-740°C to obtain a TiB2 / Al-Cu alloy ingot.
[0015] Furthermore, the amount of the Al-Y master alloy added is increased by an additional 3% to 6% on the basis of the rated amount.
[0016] In a fourth aspect, the present invention provides a TiB2 / Al-Cu alloy prepared by the above-mentioned preparation method, comprising nano-TiB2 ceramic particles dispersedly distributed in the structure and spherical nano-precipitated phases.
[0017] Furthermore, in terms of mass fraction, the TiB2 / Al-Cu alloy components include Cu: 4%; Mn: 0.2%; Y: 0.1%; TiB2: 3%, and the balance is Al.
[0018] Furthermore, the TiB2 / Al-Cu alloy ingot is powdered by vacuum air atomization: under the action of protective gas, the alloy ingot is melted at a superheat of 450-650°C to obtain an alloy ingot melt, and then vacuum air atomization is performed at an atomization pressure of 2-6 MPa to obtain TiB2 / Al-Cu alloy powder.
[0019] In a fifth aspect, the present invention provides an additive manufacturing application of a TiB2 / Al-Cu alloy, characterized in that the TiB2 / Al-Cu alloy is a powder with a particle size of 20 to 50 μm obtained by sieving the TiB2 / Al-Cu alloy powder prepared by the preparation method as described above, and is formed using a laser powder bed melting device and 3D printed layer by layer using a high-energy laser beam.
[0020] Compared with the prior art, the present invention has the following advantages or beneficial effects:
[0021] (1) The present invention innovatively adopts a mixed salt in-situ autogenous method with magnetic field vibration assisted mechanical stirring to prepare TiB2 / Al-Cu alloy, which is beneficial to promote the uniform dispersion of micro-nano TiB2 particles formed in the material, exert the heterogeneous nucleation and reinforcement effects of the particles, and can effectively improve the laser absorption rate of the alloy in the additive manufacturing process;
[0022] (2) In the present invention, trace alloying elements such as Mn, Zr / Y are added during the smelting process, which can refine the grains during the alloying process, improve the mechanical properties and corrosion resistance of the material, and the aluminum alloy obtained by gas atomization powder making has a high sphericity, which can be used for large-scale production;
[0023] (3) Since the rare earth element Y easily floats on the surface of the alloy liquid to form slag and is easily burned, the Y element is added in the present invention by adding the Al-Y master alloy at a relatively low temperature to supplement the burning loss, so as to ensure that the alloy composition ratio is not biased;
[0024] (4) The present invention refines the alloy microstructure by adding trace alloying elements (Mn, Zr / Y) and TiB2 ceramic particles to the Al-Cu alloy and makes the microstructure contain dispersed nano-TiB2 ceramic particles and spherical nano-precipitates, thereby improving the alloy's shrinkage, shrinkage, thermal cracking, segregation and other defects, and improving the laser absorption rate, so that it can be used for additive manufacturing of complex components. The obtained additive manufacturing components have uniform structure, fine grain size, high high temperature strength and corrosion resistance, providing optional materials for lightweight key equipment. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] The present invention and its features and advantages will become more apparent by reading the detailed description of non-limiting embodiments with reference to the following drawings. The same reference numerals indicate the same parts in all the drawings. The drawings are not drawn completely to scale, and emphasis is placed on illustrating the subject matter of the present invention.
[0026] Figure 1 Scanning electron microscope (SEM) images of Al-4Cu-0.2Mn-0.1Y alloy (a) and 3TiB2 / Al-4Cu-0.2Mn-0.1Y alloy (b) in Comparative Example 2 and Example 2 of the present invention;
[0027] Figure 2 This is the element EDS surface distribution diagram of the Al-4Cu-0.2Mn-0.1Y alloy in Comparative Example 2 of the present invention;
[0028] Figure 3 It is an enlarged view of different regions in the 3TiB2 / Al-4Cu-0.2Mn-0.1Y alloy in Example 2 of the present invention and its corresponding element EDS surface distribution map.
[0029] Figure 4 SEM images of Al-4Cu alloy powder (a) and 3TiB2 / Al-4Cu-0.2Mn-0.1Y alloy powder (b) in Example 4 of the present invention;
[0030] Figure 5 This is a SEM image of the deposited state of the 3D printed Al-4Cu alloy sample in Example 5 of the present invention. DETAILED DESCRIPTION
[0031] The exemplary embodiments of the present disclosure will be described in more detail below with reference to the accompanying drawings. It should be understood that all of these exemplary embodiments described are only partial embodiments and examples of the present invention, rather than all of them. On the contrary, these exemplary embodiments are provided so that those skilled in the art can more thoroughly understand the present disclosure and can more completely convey the technical content of the present disclosure to those skilled in the art.
[0032] Comparative Example 1
[0033] 400 g of Al-50Cu and 4600 g of high-purity Al with a purity of 99.9% were placed in a melting crucible in turn and melted. The temperature was raised to 780 °C for melting and stirred evenly with a stone mill rod. The melt was then cast at 730 °C to obtain an Al-4Cu alloy ingot.
[0034] Comparative Example 2
[0035] 400 g Al-50Cu, 100 g Al-10Mn and 4450 g high-purity Al with a purity of 99.9% were placed in a melting crucible in turn and melted. The temperature was raised to 780 ℃ for melting, and a transverse eddy current magnetic field was applied at the same time. The current intensity was set to 16A for 10 min. The temperature was then lowered to 700 ℃, 50 g Al-10Y intermediate alloy was added, and after stirring with a stone mill rod, a transverse eddy current magnetic field was continued to be applied for 5 min with a current of 10A. The melt was then cast at 730 ℃ to obtain an Al-4Cu-0.2Mn-0.1Y alloy ingot.
[0036] See also Figure 1 (a) and Figure 2 The grains of the Mn and Y modified Al-Cu alloy prepared by magnetic field vibration assisted mechanical stirring are non-spherical, with an average grain size of 62μm, and the Mn, Y, Al, and Cu elements are evenly distributed.
[0037] Example 1
[0038] The present embodiment provides a preparation method of a TiB2 / Al-Cu alloy and the prepared TiB2 / Al-Cu alloy. The TiB2 / Al-Cu alloy comprises, by mass fraction, 1-5% Cu, 0.1-0.3% Mn, 1-8% TiB2, and the remainder Al. The preparation process comprises the following steps:
[0039] Step S1, according to the composition ratio of the TiB2 / Al-Cu alloy, high-purity Al, Al-Cu master alloy and Al-Mn master alloy are placed in a melting crucible and melted into a melt;
[0040] Step S2, heating the melt to 760-850°C, adding KBF4 and K2TiF6 mixed salt according to the composition ratio of the TiB2 / Al-Cu alloy, applying a transverse eddy current magnetic field with a current intensity not exceeding 20A, and performing mechanical stirring; then casting the melt at 720-740°C to obtain a TiB2 / Al-Cu alloy ingot.
[0041] The melt homogenization and casting temperatures within the applicable range vary with the alloy components and are determined based on the alloy's phase diagram or melting point.
[0042] A preferred example is provided below to help those skilled in the art understand the technical solution and technical effects of the present invention.
[0043] 400g Al-50Cu, 100g Al-10Mn, and 4493.5g high-purity Al with a purity of 99.9% were placed in a melting crucible in turn and melted. The temperature was raised to 780 °C for melting, mechanical stirring was performed for 5 min, and the temperature was raised to 850 °C, 540g KBF4 and 514.5g K2TiF6 mixed salt were added, and a transverse eddy current magnetic field was applied at the same time. The current intensity was set to 16A and the implementation time was 10min. Subsequently, the melt was cast at 730 °C to obtain a 3TiB2 / Al-4Cu-0.2Mn alloy ingot. According to the electron microscope test, the elements of the 3TiB2 / Al-4Cu-0.2Mn alloy were evenly distributed, and the average grain size was 6.1μm.
[0044] Example 2
[0045] The present embodiment provides a preparation method of a TiB2 / Al-Cu alloy and the prepared TiB2 / Al-Cu alloy. The TiB2 / Al-Cu alloy comprises, by mass fraction, Cu: 1-5%; Mn: 0.1-0.3%; Y: 0.1-0.3%; TiB2: 1-8%, and the balance is Al. The preparation process comprises the following steps:
[0046] Step S1, according to the composition ratio of the TiB2 / Al-Cu alloy, high-purity Al, Al-Cu master alloy and Al-Mn master alloy are placed in a melting crucible and melted into a melt;
[0047] Step S2, heating the melt to 760-850° C., adding KBF4 and K2TiF6 mixed salt according to the composition ratio of the TiB2 / Al-Cu alloy, applying a transverse eddy current magnetic field with a current intensity of no more than 20A, and performing mechanical stirring;
[0048] Step S3, cooling the melt to 700-710°C, adding Al-Y master alloy according to the composition ratio of the TiB2 / Al-Cu alloy, continuously applying a transverse eddy current magnetic field and mechanical stirring, and adding an additional amount of Al-Y master alloy to increase the burnout amount on the basis of the rated addition amount; then casting the melt at 720-740°C to obtain a TiB2 / Al-Cu alloy ingot. The addition amount of the Al-Y master alloy is increased by 3%-6% on the basis of the rated addition amount, and the selection of the specific value is determined according to the melt processing temperature. A higher melt processing temperature will add more burnout.
[0049] A preferred example is provided below to help those skilled in the art understand the technical solution and technical effects of the present invention.
[0050] 400g Al-50Cu, 100g Al-10Mn, and 4493.5g high-purity Al with a purity of 99.9% were melted in a melting crucible in sequence, heated to 780℃, and mechanically stirred for 5 minutes. The temperature was raised to 850℃, and 540g KBF4 and 514.5g K2TiF6 mixed salt were added. At the same time, a transverse eddy current magnetic field was applied, and the current intensity was set to 16A for 10 minutes. Then the temperature was lowered to 700℃, 50g Al-10Yg intermediate alloy was added, and after stirring with a stone mill rod, a transverse eddy current magnetic field was continued to be applied for 5 minutes, with a current of 10A. Subsequently, the melt was cast at 730℃ to obtain a 3TiB2 / Al-4Cu-0.2Mn-0.1Y alloy ingot. Since the rare earth element Y easily floats on the surface of the alloy liquid to form slag and is easily burned, the Y element is added in this embodiment by adding the Al-Y master alloy at a relatively low temperature to supplement the burning loss to ensure that the alloy composition ratio is not biased.
[0051] See also Figure 1 (b) and Figure 3 The grains of TiB2, Mn, and Y modified Al-Cu alloys are non-spherical, with an average grain size of 3.8 μm, and Al6Mn nanoparticles and TiB2 nanoparticles are distributed in the alloy.
[0052] Example 3
[0053] The present embodiment provides a preparation method of a TiB2 / Al-Cu alloy and the prepared TiB2 / Al-Cu alloy. The TiB2 / Al-Cu alloy comprises, by mass fraction, Cu: 1-5%; Mn: 0.1-0.3%; Zr: 0.1-0.3%; TiB2: 1-8%, and the balance is Al. The preparation process comprises the following steps:
[0054] Step S1, according to the composition ratio of the TiB2 / Al-Cu alloy, high-purity Al, Al-Cu master alloy, Al-Mn master alloy, and Al-Zr master alloy are placed in a melting crucible and melted into a melt;
[0055] Step S2, heating the melt to 760-850°C, adding KBF4 and K2TiF6 mixed salt according to the composition ratio of the TiB2 / Al-Cu alloy, applying a transverse eddy current magnetic field with a current intensity not exceeding 20A, and performing mechanical stirring; then casting the melt at 720-740°C to obtain a TiB2 / Al-Cu alloy ingot.
[0056] The melt homogenization and casting temperatures within the applicable range vary with the alloy components and are determined based on the alloy's phase diagram or melting point.
[0057] In the TiB2 / Al-Cu alloy of this embodiment, Zr element is added to replace the Y element in Example 2, so that the preparation steps are simplified and more suitable for large-scale production.
[0058] Example 4
[0059] In this embodiment, the alloy ingots described in the comparative example and the embodiment are subjected to vacuum gas atomization powdering. More specifically, under the action of protective gas, at a superheat of 450-650°C, the alloy ingot is melted to obtain an alloy ingot melt, and then vacuum gas atomization powdering is performed at an atomization pressure of 2-6 MPa to obtain alloy powder.
[0060] A preferred example is provided below to help those skilled in the art understand the technical solution and technical effects of the present invention.
[0061] The Al-4Cu-0.2Mn-0.1Y and 3TiB2 / Al-4Cu-0.2Mn-0.1Y alloy ingots prepared in the above embodiment were subjected to vacuum gas atomization to obtain alloy powders. The gas atomization operation process was an atomization pressure of 5.5 MPa, a mass flow rate of 4.28 Kg / min, a nozzle diameter of 3.5 mm, a superheat of 500 °C, and Ar was used as a process protective gas. The powder obtained by gas atomization was sieved with a 400-mesh screen to obtain Al-4Cu-0.2Mn-0.1Y and 3TiB2 / Al-4Cu-0.2Mn-0.1Y powders with a particle size between 20 and 50 μm.
[0062] See also Figure 4 The prepared 3TiB2 / Al-4Cu-0.2Mn-0.1Y powder has a high sphericity and is suitable as a 3D printing material.
[0063] Example 5
[0064] This embodiment adopts BLT-S500 laser powder bed equipment, and uses the Al-Cu alloy and TiB2 / Al-Cu alloy powders in the above comparative examples and embodiments to perform high-energy laser beam layer-by-layer 3D printing. More specifically, the powder spreading scraper spreads the powder evenly on the forming substrate, and the laser beam melts the powder layer by layer according to the computer-designed CAD model until it accumulates into a three-dimensional block, wherein the parameter settings for laser additive manufacturing include: substrate 2024Al alloy, laser spot diameter of 70~130 μm; scanning power of 200-350 W; scanning speed of 100~500 mm / s; scanning spacing of 70~130 μm; powder spreading thickness of 30~50 μm; protective gas is Ar, its flow rate is 10~30 kg / min, and the oxygen content of the manufacturing molding system is less than 20 ppm; the scanning strategy is strip-shaped, chessboard-shaped or honeycomb-shaped, and the substrate preheating temperature is 250~400℃. A preferred example is provided below to facilitate those skilled in the art to understand the technical scheme and technical effects of the present invention.
[0065] The forming parameters are: laser spot diameter: 75 μm, scanning power: 250 W, scanning speed maintained at 300 mm / s, scanning spacing 110 μm, powder thickness 30 μm, scanning strategy is strip-shaped; substrate: 2024Al alloy; substrate preheating temperature: 350°C; protective gas is Ar, and the oxygen content is less than 20 ppm.
[0066] The laser absorption rates of Al-4Cu and TiB2 / Al-Cu are 45% and 60%, respectively. It can be seen that the uniformly dispersed micro-nano TiB2 particles in the alloy can effectively improve the laser absorption rate of the alloy during the additive manufacturing process.
[0067] After cross-sectional SEM testing, it was found that the 3D printed Al-4Cu alloy had obvious corrosion cracks (see Figure 5 ), while no obvious structural defects were found in the TiB2 / Al-Cu alloy samples. Table 1 shows the mechanical properties data of 3D-printed Al-4Cu, 3TiB2 / Al-4Cu, and 3TiB2 / Al-4Cu-0.2Mn-0.1Y alloy samples tested under the same conditions. As can be seen from the table, the structure obtained by additive manufacturing of Al-4Cu alloy with uniformly dispersed micro-nano TiB2 particles has better mechanical properties than Al-4Cu alloy. The mechanical properties of the additive manufacturing structure of TiB2 / Al-Cu alloy with micro-alloying elements such as Mn are even better. The 3D-printed Al-4Cu alloy samples and TiB2 / Al-Cu alloy samples were immersed in 3.5% NaCl solution for 30 days and then tested for surface defects. The corrosion rate of Al-4Cu alloy was 0.27mm / a, and the corrosion rate of TiB2 / Al-Cu alloy was 0.1mm / a, and no obvious signs of corrosion were found.
[0068] Table 1 Mechanical properties data of 3D printed alloy samples tested under the same conditions
[0069] Sample Tensile strength (MPa) Yield strength (MPa) Elongation (%) Al-4Cu 150 / 0.2 <![CDATA[3TiB2 / Al-4Cu]]> 375 260 5 <![CDATA[3TiB2 / Al-4Cu-0.2Mn-0.1Y]]> 450 320 6.6
[0070] In summary, the present application provides a TiB2 / Al-Cu alloy, a preparation method thereof and an additive manufacturing application. The TiB2 / Al-Cu alloy is prepared by a mixed salt in-situ autogenous method with magnetic field vibration assisted mechanical stirring, which is conducive to promoting the uniform dispersion of micro-nano TiB2 particles formed in the material, exerting the heterogeneous nucleation and strengthening effects of particles, and can effectively improve the laser absorption rate of the alloy in the additive manufacturing process; in terms of mass fraction, the basic components of the TiB2 / Al-Cu alloy are Cu: 1~5%; Mn: 0.1~0.3%; TiB2: 1~8%, and the balance is Al. Preferably, trace alloying elements such as Mn, Zr / Y are added during the smelting process, which can refine the grains during the alloying process and improve the mechanical properties and corrosion resistance of the material.
[0071] The above describes the preferred embodiments of the present invention. It should be understood that the present invention is not limited to the above-mentioned specific embodiments, and the devices and structures that are not described in detail should be understood to be implemented in a common manner in the art; any technician familiar with the art can use the above-disclosed methods and technical contents to make many possible changes and modifications to the technical solutions of the present invention without departing from the scope of the technical solutions of the present invention, or modify them into equivalent embodiments of equivalent changes, which does not affect the essential content of the present invention. Therefore, any simple modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solutions of the present invention are still within the scope of protection of the technical solutions of the present invention.
Claims
1. A method for preparing a TiB2 / Al-Cu alloy, characterized in that: In terms of mass fraction, the TiB2 / Al-Cu alloy comprises Cu: 1-5%; Mn: 0.1-0.3%; TiB2: 1-8%, and the balance is Al. The preparation process comprises the following steps: Step S1, according to the composition ratio of the TiB2 / Al-Cu alloy, high-purity Al, Al-Cu master alloy and Al-Mn master alloy are placed in a melting crucible and melted into a melt; Step S2, heating the melt to 760-850°C, adding KBF4 and K2TiF6 mixed salt according to the composition ratio of the TiB2 / Al-Cu alloy, applying a transverse eddy current magnetic field with a current intensity not exceeding 20A, and performing mechanical stirring; then casting the melt at 720-740°C to obtain a TiB2 / Al-Cu alloy ingot.
2. A method for preparing a TiB2 / Al-Cu alloy, characterized in that: In terms of mass fraction, the TiB2 / Al-Cu alloy comprises Cu: 1-5%; Mn: 0.1-0.3%; Zr: 0.1~0.3%; TiB2: 1~8%, the balance is Al; the preparation process includes the following steps: Step S1, according to the composition ratio of the TiB2 / Al-Cu alloy, high-purity Al, Al-Cu master alloy, Al-Mn master alloy, and Al-Zr master alloy are placed in a melting crucible and melted into a melt; Step S2, heating the melt to 760-850°C, adding KBF4 and K2TiF6 mixed salt according to the composition ratio of the TiB2 / Al-Cu alloy, applying a transverse eddy current magnetic field with a current intensity not exceeding 20A, and performing mechanical stirring; then casting the melt at 720-740°C to obtain a TiB2 / Al-Cu alloy ingot.
3. A method for preparing a TiB2 / Al-Cu alloy, characterized in that: In terms of mass fraction, the TiB2 / Al-Cu alloy comprises Cu: 1-5%; Mn: 0.1-0.3%; Y: 0.1~0.3%; TiB2: 1~8%, the balance is Al; the preparation process includes the following steps: Step S1, according to the composition ratio of the TiB2 / Al-Cu alloy, high-purity Al, Al-Cu master alloy and Al-Mn master alloy are placed in a melting crucible and melted into a melt; Step S2, heating the melt to 760-850° C., adding KBF4 and K2TiF6 mixed salt according to the composition ratio of the TiB2 / Al-Cu alloy, applying a transverse eddy current magnetic field with a current intensity of no more than 20A, and performing mechanical stirring; Step S3, cooling the melt to 700-710°C, adding Al-Y master alloy according to the composition ratio of the TiB2 / Al-Cu alloy, continuously applying a transverse eddy current magnetic field and mechanical stirring, and adding an amount of Al-Y master alloy to increase the burnout amount on the basis of the rated addition amount; then casting the melt at 720-740°C to obtain a TiB2 / Al-Cu alloy ingot.
4. The method for preparing a TiB2 / Al-Cu alloy according to claim 3, characterized in that: The amount of the Al-Y master alloy added is increased by an additional 3% to 6% on the basis of the rated amount.
5. A TiB2 / Al-Cu alloy, characterized in that: Prepared by the preparation method as claimed in claim 1, comprising nano-TiB2 ceramic particles and spherical nano-precipitated phases dispersed in the tissue; Calculated by mass fraction, the alloy components are Cu: 1~5%; Mn: 0.1~0.3%; TiB2: 1~8%, and the balance is Al.
6. A TiB2 / Al-Cu alloy, characterized in that: Prepared by the preparation method as claimed in claim 2, comprising nano-TiB2 ceramic particles and spherical nano-precipitated phases dispersed in the tissue; In terms of mass fraction, the alloy components are: Cu: 1~5%; Mn: 0.1~0.3%; Zr: 0.1~0.3%; TiB2: 1~8%, the balance is Al.
7. A TiB2 / Al-Cu alloy, characterized in that: Prepared by the preparation method as claimed in claim 3, comprising nano-TiB2 ceramic particles and spherical nano-precipitated phases dispersed in the tissue; In terms of mass fraction, the alloy components are: Cu: 1~5%; Mn: 0.1~0.3%; Y: 0.1~0.3%; TiB2: 1~8%, the balance is Al.
8. A TiB2 / Al-Cu alloy according to claim 7, characterized in that: In terms of mass fraction, the alloy components are: Cu: 4%; Mn: 0.2%; Y: 0.1%; TiB2: 3%, the balance is Al.
9. A method for preparing a TiB2 / Al-Cu alloy according to any one of claims 1 to 4, characterized in that: The TiB2 / Al-Cu alloy ingot is powdered by vacuum air atomization: under the action of protective gas, the alloy ingot is melted at a superheat of 450-650°C to obtain an alloy ingot melt, and then vacuum air atomization is performed at an atomization pressure of 2-6 MPa to obtain TiB2 / Al-Cu alloy powder.
10. A TiB2 / Al-Cu alloy for additive manufacturing, characterized in that: The TiB2 / Al-Cu alloy is The TiB2 / Al-Cu alloy powder prepared by the preparation method according to claim 9 is sieved to obtain a powder with a particle size of 20-50 μm, formed by a laser powder bed melting device, and 3D printed layer by layer using a high-energy laser beam.
Citation Information
Patent Citations
High-strength aluminum-base alloy products and process for production thereof
CN101558177A
High-performance in-situ TiB2 particle reinforced aluminum-based composite material and preparation method thereof
CN110129641A
Ultra high strength aluminum-base alloys
US5211910A